Conductive nickel powder / aluminum powder composite powder and preparation method thereof

By in-situ growing a ZnO@C porous composite material on the surface of aluminum powder and combining it with a replacement-reduction double nickel plating process, a stable nickel shell layer is formed, which solves the problem of weak bonding between the nickel layer and the aluminum core and achieves high conductivity and corrosion resistance.

CN120438615BActive Publication Date: 2025-09-19WUHAN BEICHEN STAR IMPORT & EXPORT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510963307.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-14
Publication Date
2025-09-19
Estimated Expiration
2045-07-14

AI Technical Summary

Technical Problem

Traditional nickel-coated aluminum powder has poor conductivity and corrosion resistance due to weak bonding between the nickel layer and the aluminum core, alumina formation and coating defects.

Method used

A ZnO@C porous composite material was formed by in-situ growth of a zinc-based metal-organic framework on the surface of micron-sized spherical aluminum powder. A stable nickel shell layer was formed by combining the replacement-reduction double nickel plating process, and a dense conductive network was formed by microwave sintering.

Benefits of technology

The prepared conductive nickel powder/aluminum powder composite powder has a low initial resistivity, and the resistivity increases slightly after the salt spray test, which significantly inhibits the penetration of corrosive media and maintains stable conductive properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120438615B_ABST
    Figure CN120438615B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of conductive metal powders, and specifically to a conductive nickel powder / aluminum powder composite powder and a preparation method thereof. Traditional nickel-coated aluminum powder has poor conductivity and corrosion resistance due to weak bonding between the nickel layer and the aluminum core, aluminum oxide generation, and coating defects. The present invention grows a zinc-based metal organic framework in situ on the surface of micron-sized spherical aluminum powder, and calcines to form a ZnO@C porous composite material. ZnO@C forms an Al-O-Zn interface bond with the aluminum matrix, which is firmly bonded to the aluminum powder. Combined with a substitution-reduction double nickel plating process, the nickel layer is embedded in the pores and interlaced with the carbon skeleton, and finally the aluminum powder is coated to form a stable nickel shell layer. Finally, microwave sintering forms a dense conductive network, which effectively inhibits the penetration of corrosive media. The obtained conductive nickel powder / aluminum powder composite powder has low initial resistivity, and the resistivity only increases slightly after the salt spray test.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of conductive metal powders, and in particular to a conductive nickel powder / aluminum powder composite powder and a preparation method thereof. Background Art

[0002] With the rapid development of electronic packaging, conductive adhesives, electromagnetic shielding and other fields, the demand for high-performance conductive powders is increasing. Composite aluminum powder prepared by coating other metal coatings on the surface of aluminum powder is often used as a conductive filler in rubber to give it electromagnetic shielding properties, which has become a research hotspot. Common types of composite aluminum powder include silver-plated aluminum powder, copper-plated aluminum powder and nickel-plated aluminum powder. Nickel-coated aluminum powder has become an ideal material to replace pure nickel powder due to its light weight, high conductivity and cost advantages. However, in the conventional chemical nickel plating process of traditional nickel-coated aluminum powder, due to the difference in thermal expansion coefficient and the obstruction of the surface oxide layer, the interface peeling is prone to occur between the nickel layer and the aluminum core, resulting in deterioration of conductivity; and aluminum powder is easily oxidized in a humid or salt spray environment to form an insulating aluminum oxide layer, which significantly increases the resistivity; a single chemical nickel plating layer is prone to pores or cracks, and the corrosive medium invades through the defects, accelerating the corrosion of the aluminum core. A Chinese patent with authorization publication number CN112207276B discloses a method for preparing micron nickel-plated aluminum powder, in which reduction nickel plating is performed on the basis of displacement nickel plating. The temperature required in the displacement reduction nickel plating process is relatively low, which reduces energy consumption and preparation costs. Since the pH required for reduction nickel plating is 7 to 8, the amount of ammonia used is significantly reduced, which reduces environmental pollution. The prepared micron nickel-plated aluminum powder has a uniform and dense coating, a high coating rate, and good conductivity, but the bonding strength between the nickel layer and the aluminum powder is not enhanced. Summary of the Invention

[0003] In view of the fact that traditional nickel-coated aluminum powder in the prior art has poor conductivity and corrosion resistance due to weak bonding between the nickel layer and the aluminum core, alumina generation, and coating defects, the present application provides a conductive nickel powder / aluminum powder composite powder and its preparation method. The present invention grows a zinc-based metal organic framework in situ on the surface of micron-sized spherical aluminum powder and calcines it to form a ZnO@C porous composite material. ZnO@C forms an Al-O-Zn interface bond with the aluminum matrix and firmly bonds to the aluminum powder. Then, combined with a displacement-reduction double nickel plating process, the nickel layer is embedded in the pores and interlaced with the carbon skeleton, finally coating the aluminum powder to form a stable nickel shell layer. Finally, microwave sintering forms a dense conductive network, which effectively inhibits the penetration of corrosive media. The obtained conductive nickel powder / aluminum powder composite powder has low initial resistivity, and the resistivity only increases slightly after the salt spray test.

[0004] To achieve the above objectives, this application adopts the following technical solutions:

[0005] In a first aspect, the present invention provides a conductive nickel powder / aluminum powder composite powder, which has a core-shell structure and includes an aluminum powder core layer and a nickel shell layer; it also includes a ZnO@C porous composite material loaded on the surface of the aluminum powder, and the precursor of the ZnO@C porous composite material is a zinc-based metal organic framework material grown in situ on the surface of the aluminum powder; the nickel shell layer is plated by a method of first replacement and then reduction, interspersed with the pores of the ZnO@C porous composite material, and coated on the outside of the aluminum powder to form the nickel shell layer.

[0006] In a second aspect, the present invention further provides a method for preparing a conductive nickel powder / aluminum powder composite powder, comprising the following steps:

[0007] S1. The micron-sized spherical aluminum powder was etched with sodium hydroxide solution and ultrasonically pretreated with hydrogen peroxide to obtain pretreated aluminum powder;

[0008] S2. Immersing the pretreated aluminum powder in a precursor solution containing a zinc source, an organic ligand, and a surfactant, allowing the reaction to proceed to obtain aluminum powder loaded with a zinc-based metal-organic framework material, which is then calcined to obtain an aluminum powder loaded with a porous composite material;

[0009] S3. The porous composite material loaded with aluminum powder was sequentially subjected to nickel displacement plating and reduction nickel plating to obtain nickel-coated aluminum powder;

[0010] S4. Sintering the nickel-coated aluminum powder by microwave in an inert reducing atmosphere to obtain a conductive nickel powder / aluminum powder composite powder.

[0011] Beneficial technical effects:

[0012] The present invention loads a ZnO@C porous composite material on the surface of micron-sized spherical aluminum powder. The ZnO in the porous composite material forms an Al-O-Zn interface bond with the aluminum matrix, making the porous composite material firmly bonded to the surface of the aluminum core. A nickel layer is then coated by a displacement-reduction double nickel plating process. In the displacement nickel plating process, nickel ions are replaced with the surface aluminum to form a displacement nickel layer. Then, reduced nickel is further grown on the displacement nickel layer by reduction nickel plating. Due to the presence of the porous structure, the growth of reduced nickel proceeds along the pores of the ZnO@C porous composite material until the aluminum powder is completely coated, thereby forming a stable nickel shell layer. Since the ZnO@C porous composite material is firmly bonded to the aluminum powder surface through the Al-O-Zn interface bond, the entire nickel-based structure is firmly bonded to the aluminum powder, avoiding the problem of easy nickel shedding. Finally, microwave sintering is used to promote the mutual diffusion of nickel powder and aluminum powder, thereby improving the density. The resulting conductive nickel powder / aluminum powder composite powder has low resistivity, and the resistivity only increases slightly after salt spray testing. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a SEM characterization image of the conductive nickel powder / aluminum powder composite powder prepared in Example 1 of the present invention.

[0014] Figure 2 Schematic diagram of the preparation method of the conductive nickel powder / aluminum powder composite powder of the present invention. DETAILED DESCRIPTION

[0015] In order to make the technical problems, technical solutions, and beneficial effects to be solved by this application more clearly understood, the present application is further described in detail below with reference to the following examples. However, this should not be construed as limiting the scope of this application to the following examples. Without departing from the above-mentioned method concepts of this application, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of this application.

[0016] In this application, the terms used in this application are for the purpose of describing specific embodiments only and are not intended to be limiting of the application.

[0017] As used in this application, the singular forms "for," "or," "an," "any," and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0018] In addition, the terms “first” and “second”, if used, are only used for descriptive purposes and should not be understood as indicating or implying relative importance.

[0019] In a first aspect, the present invention provides a conductive nickel powder / aluminum powder composite powder, which has a core-shell structure and includes an aluminum powder core layer and a nickel shell layer; it also includes a ZnO@C porous composite material loaded on the surface of the aluminum powder, and the precursor of the ZnO@C porous composite material is a zinc-based metal organic framework material grown in situ on the surface of the aluminum powder; the nickel shell layer is plated by a method of first replacement and then reduction, interspersed with the pores of the ZnO@C porous composite material, and coated on the outside of the aluminum powder to form the nickel shell layer.

[0020] In a feasible implementation scenario, the aluminum powder is micron-sized spherical aluminum powder with a particle size of 20-50 μm; and the thickness of the nickel shell layer is 0.1-1 μm.

[0021] In a feasible implementation, the particle size of the conductive nickel powder / aluminum powder composite powder is 20-50 μm.

[0022] In a second aspect, the present invention also provides a method for preparing a conductive nickel powder / aluminum powder composite powder, comprising the following steps:

[0023] S1. The micron-sized spherical aluminum powder was etched with sodium hydroxide solution and ultrasonically pretreated with hydrogen peroxide to obtain pretreated aluminum powder;

[0024] S2. Immersing the pretreated aluminum powder in a precursor solution containing a zinc source, an organic ligand, and a surfactant, allowing the reaction to proceed to obtain aluminum powder loaded with a zinc-based metal-organic framework material, which is then calcined to obtain an aluminum powder loaded with a porous composite material;

[0025] S3. The porous composite material loaded with aluminum powder was sequentially subjected to nickel displacement plating and reduction nickel plating to obtain nickel-coated aluminum powder;

[0026] S4. Sintering the nickel-coated aluminum powder by microwave in an inert reducing atmosphere to obtain a conductive nickel powder / aluminum powder composite powder.

[0027] In a feasible implementation scenario, the concentration of the sodium hydroxide solution in S1 is 8-12 wt %, and the etching time is until a large number of bubbles are generated; the concentration of the hydrogen peroxide solution is 2-5 wt %.

[0028] In a feasible implementation scenario, the zinc source in S2 is zinc nitrate, the organic ligand is 2-methylimidazole, and the molar ratio of the zinc source to the organic ligand is 1:3-1:5; the surfactant is hexadecyltrimethylammonium bromide, and the amount of the surfactant added is 0.5% to 1.5% of the total mass of the precursor solution.

[0029] In a feasible implementation, the calcination in S2 is carried out in a nitrogen atmosphere, the calcination temperature is 350-450° C., and the holding time is 1-3 hours.

[0030] The surface of aluminum powder is loaded with zinc-based metal organic framework ZIF-8, which is converted into ZnO@C porous composite material through calcination. ZnO forms Al-O-Zn interface bonds with the aluminum matrix, enhancing the bonding force and preventing coating peeling; the carbon skeleton acts as an electron transmission medium, accelerating the reduction deposition of nickel ions and improving the density of the coating.

[0031] In a feasible implementation, the replacement nickel plating solution in S3 comprises nickel sulfate hexahydrate, boric acid and ammonium fluoride; and the reduction nickel plating solution comprises nickel sulfate hexahydrate, sodium dihydrogen hypophosphite, citric acid, thiourea and brightener.

[0032] In a feasible implementation, the temperature of the displacement nickel plating in S3 is 35-45° C., and the time is 5-15 minutes; the temperature of the reduction nickel plating is 55-65° C., and the time is 2-4 hours.

[0033] In the displacement nickel plating solution, the aluminum on the surface of the aluminum powder undergoes a replacement reaction with nickel ions to form an initial nickel layer, filling the bottom of the pores. During the reduction nickel plating process, sodium hypophosphite reduces the nickel ions, and the nickel continues to grow upward along the pores, interlacing with the carbon skeleton to form a continuous conductive network. The double coating covers the inside and outside of the pores, eliminating the pores and cracks of the single coating and achieving an "anchored" bond.

[0034] In a feasible implementation, the sintering temperature of the microwave sintering in S4 is 380-420° C.; and the inert reducing atmosphere is an Ar / H 2 mixed gas with a volume ratio of 95:5.

[0035] The rapid microwave heating in the Ar / H2 mixed gas promotes the diffusion of atoms between the nickel layer and the aluminum core, improves the density, and reduces cracks and pores.

[0036] The following will describe in detail a conductive nickel powder / aluminum powder composite powder and a preparation method thereof provided by the present application in combination with different embodiments.

[0037] Example 1:

[0038] like Figure 2 As shown, a method for preparing a conductive nickel powder / aluminum powder composite powder comprises the following steps:

[0039] 1. Add spherical aluminum powder with a particle size of 20-50µm into 8wt% sodium hydroxide solution, stir until a large number of bubbles appear, add a large amount of deionized water to dilute, filter and continue to wash with deionized water until neutral to obtain etched aluminum powder; immerse the etched aluminum powder in 2wt% hydrogen peroxide solution, ultrasonicate at 40℃ and 100W power for 10 minutes, filter and vacuum dry to obtain pretreated aluminum powder;

[0040] 2. Methanol and water were mixed in a volume ratio of 3:1 to obtain a mixed solvent, 0.1 mol of zinc nitrate hexahydrate was added to 1 L of the mixed solvent, and the mixture was stirred until completely dissolved. 0.3 mol of 2-methylimidazole was added and stirred, and 0.5% of the total mass of the solution of hexadecyltrimethylammonium bromide was added, and the mixture was stirred at 500 rpm for 10 min to obtain a precursor solution; 10 g of pretreated aluminum powder was added to 1 L of the precursor solution, ultrasonically treated at 100 W for 5 min, and allowed to stand at room temperature for 12 h, gently shaken 5 times every 2 h, and washed with methanol after the reaction was completed. The precursor-loaded aluminum powder was dried in a vacuum at 60 ° C to obtain a precursor-loaded aluminum powder; the precursor-loaded aluminum powder was placed in a tube furnace, calcined at 350 ° C under a nitrogen atmosphere, with a heating rate of 5 ° C / min and a holding time of 3 h, and cooled with the furnace to obtain aluminum powder loaded on a porous composite material;

[0041] 3. Dissolve 80 parts of nickel sulfate hexahydrate and 15 parts of boric acid in 1000 parts of deionized water, add 8 parts of ammonium fluoride, and adjust the pH to 4.8 with dilute sulfuric acid to obtain a displacement nickel plating solution. Immerse 1 part of aluminum powder supported by the porous composite material in 20 parts of the displacement nickel plating solution, stir at 200 rpm at 35°C for 15 minutes, and then filter, wash, and dry to obtain the displacement nickel-coated aluminum powder;

[0042] 4. Dissolve 100 parts of nickel sulfate hexahydrate, 75 parts of sodium dihydrogen hypophosphite, 55 parts of citric acid, 3 parts of thiourea and 0.3 parts of sodium saccharin in 1000 parts of deionized water, adjust the pH to 6.5 with ammonia water to obtain a reduction nickel plating solution, immerse 1 part of the replaced nickel-coated aluminum powder in 20 parts of the reduction nickel plating solution, and stir at 200 rpm at 55°C for 4 hours to obtain nickel-coated aluminum powder;

[0043] 5. Spread nickel-coated aluminum powder on a quartz boat, place it in a microwave sintering furnace, introduce Ar / H2 mixed gas, the Ar / H2 volume ratio is 95:5, the flow rate is 50 mL / min, start microwave heating after 10 minutes, the power is 800 W, the temperature is 380 ° C, the heating rate is 50 ° C / min, the holding time is 10 minutes, and naturally cool to obtain a conductive nickel powder / aluminum powder composite powder.

[0044] Example 2:

[0045] like Figure 2 As shown, a method for preparing a conductive nickel powder / aluminum powder composite powder comprises the following steps:

[0046] 1. Add spherical aluminum powder with a particle size of 20-50µm into a 12wt% sodium hydroxide solution, stir until a large number of bubbles appear, add a large amount of deionized water to dilute, filter and continue to wash with deionized water until neutral to obtain etched aluminum powder; immerse the etched aluminum powder in a 5wt% hydrogen peroxide solution, ultrasonicate at 40℃ and 100W power for 10 minutes, filter and vacuum dry to obtain pretreated aluminum powder;

[0047] 2. Methanol and water were mixed in a volume ratio of 3:1 to obtain a mixed solvent, 0.1 mol of zinc nitrate hexahydrate was added to 1 L of the mixed solvent, and the mixture was stirred until completely dissolved. 0.5 mol of 2-methylimidazole was then added and stirred. 1.5% of the total mass of the solution was added with hexadecyltrimethylammonium bromide, and the mixture was stirred at 500 rpm for 10 min to obtain a precursor solution. 10 g of pretreated aluminum powder was added to 1 L of the precursor solution, ultrasonically treated at 100 W for 5 min, and allowed to stand at room temperature for 12 h, gently shaken 5 times every 2 h, and washed with methanol after the reaction was completed. The precursor-loaded aluminum powder was dried in a vacuum at 60 ° C to obtain the precursor-loaded aluminum powder. The precursor-loaded aluminum powder was placed in a tube furnace, calcined at 450 ° C under a nitrogen atmosphere, with a heating rate of 5 ° C / min and a holding time of 1 h. The porous composite material-loaded aluminum powder was cooled with the furnace to obtain the aluminum powder.

[0048] 3. Dissolve 80 parts of nickel sulfate hexahydrate and 15 parts of boric acid in 1000 parts of deionized water, add 8 parts of ammonium fluoride, and adjust the pH to 4.8 with dilute sulfuric acid to obtain a displacement nickel plating solution. Immerse 1 part of aluminum powder supported by the porous composite material in 20 parts of the displacement nickel plating solution, stir at 200 rpm at 45°C for 5 minutes, and then filter, wash, and dry to obtain the displacement nickel-coated aluminum powder;

[0049] 4. Dissolve 100 parts of nickel sulfate hexahydrate, 75 parts of sodium dihydrogen hypophosphite, 55 parts of citric acid, 3 parts of thiourea and 0.3 parts of sodium saccharin in 1000 parts of deionized water, adjust the pH to 6.5 with ammonia water to obtain a reduction nickel plating solution, immerse 1 part of the replaced nickel-coated aluminum powder in 20 parts of the reduction nickel plating solution, and stir at 200 rpm at 65°C for 2 hours to obtain nickel-coated aluminum powder;

[0050] 5. Spread nickel-coated aluminum powder flatly on a quartz boat, place it in a microwave sintering furnace, introduce Ar / H2 mixed gas, the Ar / H2 volume ratio is 95:5, the flow rate is 50 mL / min, start microwave heating after 10 minutes, the power is 800 W, the temperature is 420 ° C, the heating rate is 50 ° C / min, the holding time is 10 minutes, and naturally cool to obtain a conductive nickel powder / aluminum powder composite powder.

[0051] Example 3:

[0052] like Figure 2 As shown, a method for preparing a conductive nickel powder / aluminum powder composite powder comprises the following steps:

[0053] 1. Add spherical aluminum powder with a particle size of 20-50µm into a 10wt% sodium hydroxide solution, stir until a large number of bubbles appear, add a large amount of deionized water to dilute, filter and continue to wash with deionized water until neutral to obtain etched aluminum powder; immerse the etched aluminum powder in a 3wt% hydrogen peroxide solution, ultrasonicate at 40℃ and 100W power for 10 minutes, filter and vacuum dry to obtain pretreated aluminum powder;

[0054] 2. Methanol and water were mixed in a volume ratio of 3:1 to obtain a mixed solvent, 0.1 mol of zinc nitrate hexahydrate was added to 1 L of the mixed solvent, and the mixture was stirred until completely dissolved. 0.4 mol of 2-methylimidazole was then added and stirred. 1.0% of the total mass of the solution was added with hexadecyltrimethylammonium bromide, and the mixture was stirred at 500 rpm for 10 min to obtain a precursor solution. 10 g of pretreated aluminum powder was added to 1 L of the precursor solution, ultrasonically treated at 100 W for 5 min, and allowed to stand at room temperature for 12 h, gently shaken 5 times every 2 h, and washed with methanol after the reaction was completed. The precursor-loaded aluminum powder was dried in a vacuum at 60 ° C to obtain the precursor-loaded aluminum powder. The precursor-loaded aluminum powder was placed in a tube furnace, calcined at 400 ° C under a nitrogen atmosphere, with a heating rate of 5 ° C / min and a holding time of 2 h. The porous composite material-loaded aluminum powder was cooled with the furnace to obtain the aluminum powder.

[0055] 3. Dissolve 80 parts of nickel sulfate hexahydrate and 15 parts of boric acid in 1000 parts of deionized water, add 8 parts of ammonium fluoride, and adjust the pH to 4.8 with dilute sulfuric acid to obtain a displacement nickel plating solution. Immerse 1 part of aluminum powder supported by the porous composite material in 20 parts of the displacement nickel plating solution, stir at 200 rpm for 10 minutes at 40°C, and then filter, wash, and dry to obtain the displacement nickel-coated aluminum powder.

[0056] 4. Dissolve 100 parts of nickel sulfate hexahydrate, 75 parts of sodium dihydrogen hypophosphite, 55 parts of citric acid, 3 parts of thiourea and 0.3 parts of sodium saccharin in 1000 parts of deionized water, adjust the pH to 6.5 with ammonia water to obtain a reduction nickel plating solution, immerse 1 part of the replacement nickel-coated aluminum powder in 20 parts of the reduction nickel plating solution, and stir at 200 rpm at 60°C for 3 hours to obtain nickel-coated aluminum powder;

[0057] 5. Spread nickel-coated aluminum powder on a quartz boat, place it in a microwave sintering furnace, introduce Ar / H2 mixed gas with an Ar / H2 volume ratio of 95:5 and a flow rate of 50 mL / min. After 10 minutes, start microwave heating with a power of 800 W, a temperature of 400°C, a heating rate of 50°C / min, and a holding time of 10 minutes. Cool naturally to obtain a conductive nickel powder / aluminum powder composite powder.

[0058] Comparative Example 1:

[0059] like Figure 2 As shown, a method for preparing a conductive nickel powder / aluminum powder composite powder comprises the following steps:

[0060] 1. Add spherical aluminum powder with a particle size of 20-50µm into a 10wt% sodium hydroxide solution, stir until a large number of bubbles appear, add a large amount of deionized water to dilute, filter and continue to wash with deionized water until neutral to obtain etched aluminum powder; immerse the etched aluminum powder in a 3wt% hydrogen peroxide solution, ultrasonicate at 40℃ and 100W power for 10 minutes, filter and vacuum dry to obtain pretreated aluminum powder;

[0061] 2. Dissolve 80 parts of nickel sulfate hexahydrate and 15 parts of boric acid in 1000 parts of deionized water, add 8 parts of ammonium fluoride, and adjust the pH to 4.8 with dilute sulfuric acid to obtain a displacement nickel plating solution. Immerse 1 part of pretreated aluminum powder in 20 parts of the displacement nickel plating solution, stir at 200 rpm for 10 minutes at 40°C, and then filter, wash, and dry to obtain a displacement nickel-coated aluminum powder;

[0062] 3. Dissolve 100 parts of nickel sulfate hexahydrate, 75 parts of sodium dihydrogen hypophosphite, 55 parts of citric acid, 3 parts of thiourea and 0.3 parts of sodium saccharin in 1000 parts of deionized water, adjust the pH to 6.5 with aqueous ammonia to obtain a reduction nickel plating solution, immerse 1 part of the replaced nickel-coated aluminum powder in 20 parts of the reduction nickel plating solution, and stir at 200 rpm at 60°C for 3 hours to obtain nickel-coated aluminum powder;

[0063] 4. Spread nickel-coated aluminum powder flatly on a quartz boat, place it in a microwave sintering furnace, introduce Ar / H2 mixed gas with an Ar / H2 volume ratio of 95:5 and a flow rate of 50 mL / min. After 10 minutes, start microwave heating with a power of 800 W, a temperature of 400°C, a heating rate of 50°C / min, and a holding time of 10 minutes. Cool naturally to obtain a conductive nickel powder / aluminum powder composite powder.

[0064] Comparative Example 2:

[0065] like Figure 2 As shown, a method for preparing a conductive nickel powder / aluminum powder composite powder comprises the following steps:

[0066] 1. Add spherical aluminum powder with a particle size of 20-50µm into a 10wt% sodium hydroxide solution, stir until a large number of bubbles appear, add a large amount of deionized water to dilute, filter and continue to wash with deionized water until neutral to obtain etched aluminum powder; immerse the etched aluminum powder in a 3wt% hydrogen peroxide solution, ultrasonicate at 40℃ and 100W power for 10 minutes, filter and vacuum dry to obtain pretreated aluminum powder;

[0067] 2. Methanol and water were mixed in a volume ratio of 3:1 to obtain a mixed solvent, 0.1 mol of zinc nitrate hexahydrate was added to 1 L of the mixed solvent, and the mixture was stirred until completely dissolved. 0.4 mol of 2-methylimidazole was then added and stirred. 1.0% of the total mass of the solution was added with hexadecyltrimethylammonium bromide, and the mixture was stirred at 500 rpm for 10 min to obtain a precursor solution. 10 g of pretreated aluminum powder was added to 1 L of the precursor solution, ultrasonically treated at 100 W for 5 min, and allowed to stand at room temperature for 12 h, gently shaken 5 times every 2 h, and washed with methanol after the reaction was completed. The precursor-loaded aluminum powder was dried in a vacuum at 60 ° C to obtain the precursor-loaded aluminum powder. The precursor-loaded aluminum powder was placed in a tube furnace, calcined at 400 ° C under a nitrogen atmosphere, with a heating rate of 5 ° C / min and a holding time of 2 h. The porous composite material-loaded aluminum powder was cooled with the furnace to obtain the aluminum powder.

[0068] 3. Dissolve 80 parts of nickel sulfate hexahydrate and 15 parts of boric acid in 1000 parts of deionized water, add 8 parts of ammonium fluoride, and adjust the pH to 4.8 with dilute sulfuric acid to obtain a displacement nickel plating solution. Immerse 1 part of aluminum powder supported by the porous composite material in 20 parts of the displacement nickel plating solution, stir at 200 rpm for 10 minutes at 40°C, and then filter, wash, and dry to obtain the displacement nickel-coated aluminum powder.

[0069] 4. Spread the replaced nickel-coated aluminum powder on a quartz boat, place it in a microwave sintering furnace, introduce Ar / H2 mixed gas, the Ar / H2 volume ratio is 95:5, the flow rate is 50 mL / min, start microwave heating after 10 minutes, the power is 800 W, the temperature is 400 ° C, the heating rate is 50 ° C / min, the holding time is 10 minutes, and naturally cool to obtain a conductive nickel powder / aluminum powder composite powder.

[0070] Comparative Example 3:

[0071] like Figure 2 As shown, a method for preparing a conductive nickel powder / aluminum powder composite powder comprises the following steps:

[0072] 1. Add spherical aluminum powder with a particle size of 20-50µm into a 10wt% sodium hydroxide solution, stir until a large number of bubbles appear, add a large amount of deionized water to dilute, filter and continue to wash with deionized water until neutral to obtain etched aluminum powder; immerse the etched aluminum powder in a 3wt% hydrogen peroxide solution, ultrasonicate at 40℃ and 100W power for 10 minutes, filter and vacuum dry to obtain pretreated aluminum powder;

[0073] 2. Methanol and water were mixed in a volume ratio of 3:1 to obtain a mixed solvent. 0.1 mol of zinc nitrate hexahydrate was added to 1 L of the mixed solvent and stirred until completely dissolved. 0.4 mol of 2-methylimidazole was then added and stirred. 1.0% of the total mass of the solution was added with hexadecyltrimethylammonium bromide and stirred at 500 rpm for 10 min to obtain a precursor solution. 10 g of pretreated aluminum powder was added to 1 L of the precursor solution and ultrasonically treated at 100 W for 5 min. The solution was allowed to stand at room temperature for 12 h, and gently shaken 5 times every 2 h. After the reaction, the solution was washed with methanol and dried in vacuo at 60 °C to obtain a precursor-loaded aluminum powder.

[0074] 3. Dissolve 80 parts of nickel sulfate hexahydrate and 15 parts of boric acid in 1000 parts of deionized water, add 8 parts of ammonium fluoride, and adjust the pH to 4.8 with dilute sulfuric acid to obtain a displacement nickel plating solution. Immerse 1 part of the precursor-loaded aluminum powder in 20 parts of the displacement nickel plating solution, stir at 200 rpm for 10 minutes at 40°C, then filter, wash, and dry to obtain the displacement nickel-coated aluminum powder;

[0075] 4. Dissolve 100 parts of nickel sulfate hexahydrate, 75 parts of sodium dihydrogen hypophosphite, 55 parts of citric acid, 3 parts of thiourea and 0.3 parts of sodium saccharin in 1000 parts of deionized water, adjust the pH to 6.5 with ammonia water to obtain a reduction nickel plating solution, immerse 1 part of the replacement nickel-coated aluminum powder in 20 parts of the reduction nickel plating solution, and stir at 200 rpm at 60°C for 3 hours to obtain nickel-coated aluminum powder;

[0076] 5. Spread nickel-coated aluminum powder on a quartz boat, place it in a microwave sintering furnace, introduce Ar / H2 mixed gas with an Ar / H2 volume ratio of 95:5 and a flow rate of 50 mL / min. After 10 minutes, start microwave heating with a power of 800 W, a temperature of 400°C, a heating rate of 50°C / min, and a holding time of 10 minutes. Cool naturally to obtain a conductive nickel powder / aluminum powder composite powder.

[0077] Performance testing:

[0078] The conductive nickel powder / aluminum powder composite powders prepared in Examples 1-3 and Comparative Examples 1-3 of the present application were subjected to an initial resistivity test, and then the conductivity was tested after 48 hours of a salt spray test. The salt spray test was performed in accordance with GB / T 10125-2021. The test results are shown in Table 1.

[0079] Table 1 Test results of Examples 1-3 and Comparative Examples 1-3

[0080]

[0081] As shown in Table 1, the initial resistivity of Examples 1-3 is 10 -4 -10 -5 Ω·cm level, the resistivity only increased slightly after 48 hours of salt spray test and remained at 10 -4 -10 -5 Ω·cm range, indicating that its conductive performance is stable. Among them, Example 3 has the best comprehensive performance, with an initial resistivity of 8.3×10 -5 Ω·cm, after salt spray 8.8×10 -5 The resistivity increased only slightly after salt spray, indicating that the nickel shell and the ZnO@C porous composite material synergistically protected the aluminum core and effectively blocked the penetration of corrosive media. Figure 1 This is the SEM electron microscope image of the conductive nickel powder / aluminum powder composite powder prepared in Example 1. It can be seen that the composite powder is spherical, evenly coated with a nickel layer, has no obvious pores, and has evenly distributed spherical or hemispherical tiny protrusions on the surface. It is a nickel-coated ZnO@C porous composite material loaded on the surface of aluminum powder.

[0082] This is because in Examples 1-3, the surface of the aluminum powder is loaded with a zinc-based metal organic framework ZIF-8, which is converted into a ZnO@C porous composite material by calcination. ZnO forms an Al-O-Zn interface bond with the aluminum matrix, enhancing the bonding force and preventing the coating from peeling off; the carbon skeleton acts as an electron transport medium, accelerating the reduction deposition of nickel ions and improving the density of the coating. In the displacement nickel plating solution, the zinc on the surface of the aluminum powder undergoes a displacement reaction with the nickel ions to form an initial nickel layer, filling the bottom of the pores. During the reduction nickel plating process, sodium hypophosphite reduces the nickel ions, and the nickel continues to grow along the pores, interlacing with the carbon skeleton to form a continuous conductive network. The double coating covers the inside and outside of the pores, eliminating the pores and cracks of the single coating and achieving an "anchored" bond. The rapid microwave heating in the Ar / H2 mixed gas promotes atomic diffusion between the nickel layer and the aluminum core, improving the density. The pores of the ZnO@C porous composite material provide anchor points for the nickel layer, and the displacement-reduction double plating process forms a dense conductive network. The two work together to significantly inhibit the resistivity degradation caused by salt spray corrosion. The resistivity of the embodiment group remains at 10 -4 The Ω·cm level proves that the composite powder still has stable conductive properties under harsh environments. The nickel in the pores is densely filled, and even if the surface is slightly oxidized, the internal conductive network remains intact.

[0083] Comparative Example 1: Aluminum powder was directly subjected to nickel plating by replacement-reduction without introducing ZnO@C porous composite material. The initial resistivity was as high as 2.5×10 -3Ω·cm, which surged by 36.0% after salt spray. The nickel layer and the aluminum core were only bonded by physical adsorption, lacking Al-O-Zn chemical bond anchoring. The coating was easy to peel off. The aluminum core was directly exposed after the salt spray test, and insulating aluminum oxide was generated on the surface, which increased the resistivity.

[0084] In Comparative Example 2, only displacement nickel plating was performed without reduction nickel plating. The resistivity increased by 27.1% after salt spray. Displacement nickel plating relies on the replacement reaction of aluminum and nickel ions. The rate is fast but the coverage is uneven, forming a loose and porous coating. The nickel layer is thin and discontinuous, with microcracks and pores. The corrosive medium invades through the microcracks, local pitting destroys the conductive path, and the resistivity increases.

[0085] In Comparative Example 3, the aluminum powder loaded with ZIF-8 was not calcined and nickel plating was performed directly. The resistivity increased by 35.5% after salt spray. ZIF-8 was not pyrolyzed into a ZnO@C porous composite material, which resulted in the nickel plating solution being unable to penetrate along the pores. The nickel layer only covered the surface of the aluminum powder and was not embedded in the porous skeleton. The bonding strength with the aluminum core was poor. During salt spray corrosion, the interface between the coating and the aluminum core was easily peeled off, and the corrosion spread along the interface, causing the nickel layer to be damaged and peeled off, and the resistivity increased.

[0086] The above results show and describe the basic principles and main features of this application as well as the advantages of this application.

[0087] Those skilled in the art should understand that the present application is not limited to the above-described embodiments. The above-described embodiments and descriptions are merely illustrative of the principles of the present application. Various changes and improvements may be made to the present application without departing from the spirit and scope of the present application. Such changes and improvements are intended to fall within the scope of the present application. The scope of protection claimed in the present application is defined by the equivalents of the appended claims.

Claims

1. A conductive nickel powder / aluminum powder composite powder, characterized in that: The conductive nickel powder / aluminum powder composite powder has a core-shell structure, including an aluminum powder core layer and a nickel shell layer; it also includes a ZnO@C porous composite material supported on the surface of the aluminum powder, and the precursor of the ZnO@C porous composite material is a zinc-based metal organic framework material grown in situ on the surface of the aluminum powder; the nickel shell layer is plated by a method of first displacement and then reduction, interspersed with the pores of the ZnO@C porous composite material, and coated on the outside of the aluminum powder to form the nickel shell layer.

2. The conductive nickel powder / aluminum powder composite powder according to claim 1, characterized in that: The aluminum powder is micron-grade spherical aluminum powder with a particle size of 20-50 μm; the thickness of the nickel shell layer is 0.1-1 μm.

3. The conductive nickel powder / aluminum powder composite powder according to claim 1, characterized in that: The particle size of the conductive nickel powder / aluminum powder composite powder is 20-50 μm.

4. A method for preparing a conductive nickel powder / aluminum powder composite powder, characterized in that: The following steps are involved: S1. The micron-sized spherical aluminum powder was etched with sodium hydroxide solution and ultrasonically pretreated with hydrogen peroxide to obtain pretreated aluminum powder; S2. Immersing the pretreated aluminum powder in a precursor solution containing a zinc source, an organic ligand, and a surfactant, allowing the reaction to proceed to obtain aluminum powder loaded with a zinc-based metal-organic framework material, which is then calcined to obtain an aluminum powder loaded with a porous composite material; S3. The porous composite material loaded with aluminum powder was sequentially subjected to nickel displacement plating and reduction nickel plating to obtain nickel-coated aluminum powder; S4. Sintering the nickel-coated aluminum powder by microwave in an inert reducing atmosphere to obtain a conductive nickel powder / aluminum powder composite powder.

5. The method for preparing a conductive nickel powder / aluminum powder composite powder according to claim 4, characterized in that: The concentration of the sodium hydroxide solution in S1 is 8-12 wt %, and the etching time is until a large number of bubbles are generated; the concentration of the hydrogen peroxide solution is 2-5 wt %.

6. The method for preparing a conductive nickel powder / aluminum powder composite powder according to claim 4, characterized in that: S2 The zinc source is zinc nitrate, the organic ligand is 2-methylimidazole, and the molar ratio of the zinc source to the organic ligand is 1:3-1:5; the surfactant is hexadecyltrimethylammonium bromide, and the amount of the surfactant added is 0.5% to 1.5% of the total mass of the precursor solution.

7. The method for preparing a conductive nickel powder / aluminum powder composite powder according to claim 4, characterized in that: The calcination in S2 is carried out in a nitrogen atmosphere, the calcination temperature is 350-450° C., and the holding time is 1-3 hours.

8. The method for preparing a conductive nickel powder / aluminum powder composite powder according to claim 4, characterized in that: The plating solution for the displacement nickel plating in S3 comprises nickel sulfate hexahydrate, boric acid and ammonium fluoride; the plating solution for the reduction nickel plating comprises nickel sulfate hexahydrate, sodium dihydrogen hypophosphite, citric acid, thiourea and a brightener.

9. The method for preparing a conductive nickel powder / aluminum powder composite powder according to claim 4, characterized in that: The displacement nickel plating temperature in S3 is 35-45° C. and the time is 5-15 minutes; the reduction nickel plating temperature is 55-65° C. and the time is 2-4 hours.

10. The method for preparing a conductive nickel powder / aluminum powder composite powder according to claim 4, characterized in that: The microwave sintering temperature in step S4 is 380-420° C.; the inert reducing atmosphere is an Ar / H 2 mixed gas with a volume ratio of 95:5.

Citation Information

Patent Citations

  • A method for preparing micron-sized nickel-aluminum plating powder

    CN112207276B

  • Nickel package aluminum powder and preparing method thereof

    CN103433485A

  • Nickel-coated aluminum powder and preparation method thereof

    CN117467991A